PHYTOCHEMISTRY SCREENING AND ANTIOXIDANT ACTIVITY ASSAY USING DDPH OF TAYA (Nauclea orientalis) ETHANOL LEAF EXTRACT - Wahyu Nugroho; Denada A.C (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2018)
This study aims to perform phytochemical screening and antioxidant test on Taya ethanol leaf extract (Nauclea orientalis). The ethanol extract was obtained by extracting the leaves of Taya by 10 grams using 100 mL of ethanol, macerated for 3 Ã— 24 hours at room temperature then sealed, then filtered to obtain the filtrate, then concentrated. The extract is then used to identify secondary metabolites of alkaloids, flavonoids, terpenoids, steroids, saponins and phenolics. The antioxidant activity of the ethanol extract was measured by DPPH. The results showed that Taya plant leaves contained a group of secondary metabolite compounds of alkaloids, terpenoids, flavonoids, saponins and phenolics, while for steroids were not identified. The results of antioxidant activity test extract showed that ethanol extract have antioxidant activity with IC50 value that is 352,251 ppm.